Changes in and relationships between human milk oligosaccharides and microRNAs in milk-derived extracellular vesicles during the first 4 months of lactation - Morozumi, Mai; Izumi, Hirohisa; Tsuda, Muneya; Tabata, Fuka; Nakamura, Hirohiko; Miyaji, Kazuhiro (Frontiers in Nutrition, 2025)
BackgroundHuman milk oligosaccharides (HMOs) exert beneficial effects on the gut microbiota, enhance resistance to infections, support immune development, and contribute to brain/cognitive development. Milk-derived extracellular vesicles (MEVs) contain a high abundance of immunity- and development-related microRNAs (miRNAs). These components are abundant in breast milk. In the case of HMOs, the composition varies due to factors such as lactation stages, geographic location, ethnicity, genetics, and the environment. The composition of HMOs is significantly influenced by the genetic status of two key genes: FUT2 (Secretor gene) and FUT3 (Lewis gene). In this study, we broadly categorized them as secretors or non-secretors.MethodsWe investigated the changes in the concentrations of HMOs and MEVs during 4 months of lactation in Japanese women and explored the relationship between HMOs and miRNAs present in MEVs.ResultsThe concentrations of most HMOs significantly decreased over time. The number of MEVs did not change significantly over the study period. Interestingly, 3′-sialyllactose and lacto-N-fucopentaose III were inversely correlated with many of the top 20 most abundant miRNAs. Moreover, miRNAs in MEVs, which are associated with immunity and development, were more abundant in secretors than in non-secretors during early lactation. Several HMOs were detected in MEVs.ConclusionThis study enabled a detailed characterization of changes in HMOs and MEVs in the breast milk of Japanese women throughout the course of the first 4 months of lactation. A potential association between the concentrations of HMOs and miRNAs was also observed, suggesting that these components might influence each other. These findings are significant for promoting healthy infant development and growth, as well as for improving infant formula composition.